Approach Academia and Professional Practice Trough Research by Design - Menezes de Sequeira, João Manuel Barbosa (ICONARCH International Congress of Architecture and Planning, 2014)
This paper will try to stress that the approximation between academia and professional practice has its roots on the revolution that occurs in the schools of architecture in the beginnings of the XX century. And this revolution has its origin in the idea of connecting arts and crafts and then the idea of bringing practitioners into the academia and changing the concept of academic curriculum. We think that the consolidation of this approximation can be done if we consider architectural research by design as the main path to develop. This paper result of the lecture made in the 21th of November in Konya at the occasion of the seventh session of the 2nd International Congress of Architecture (ICONARCH II) under the theme “New approaches in architecture and urban planning in education”.